Development of a portable quality control application using a tablet‐type electronic device. Issue 3 (19th February 2018) - Ono, Tomohiro; Miyabe, Yuki; Akimoto, Mami; Mukumoto, Nobutaka; Ishihara, Yoshitomo; Nakamura, Mitsuhiro; Mizowaki, Takashi
Abstract : Purpose: Our aim was to develop a portable quality control (QC) application using a thermometer, a barometer, an angle gauge, and a range finder implemented in a tablet‐type consumer electronic device (CED) and to assess the accuracies of the measurements made. Methods: The QC application was programmed using Java and OpenCV libraries. First, temperature and atmospheric pressure were measured over 30 days using the temperature and pressure sensors of the CED and compared with those measured by a double‐tube thermometer and a digital barometer. Second, the angle gauge was developed using the accelerometer of the CED. The roll and pitch angles of the CED were measured from 0 to 90° at intervals of 10° in the clockwise (CW) and counterclockwise (CCW) directions. The values were compared with those measured by a digital angle gauge. Third, a range finder was developed using the tablet's built‐in camera and image‐processing capacities. Surrogate markers were detected by the camera and their positions converted to actual positions using a homographic transformation method. Fiducial markers were placed on a treatment couch and moved 100 mm in 10‐mm steps in both the lateral and longitudinal directions. The values were compared with those measured by the digital output of the treatment couch. The differences between CED values and those of other devices were compared by calculating means ± standard deviations (SDs). Results: The means ± SDs of differences in temperature and atmospheric pressure were −0.07 ± 0.25°C and 0.05 ± 0.10 hPa, respectively. The means ± SDs of the difference in angle was −0.17 ± 0.87° (0.15 ± 0.23° degrees excluding the 90° angle). The means ± SDs of distances were 0.01 ± 0.07 mm in both the lateral and longitudinal directions. Conclusions: Our portable QC application was accurate and may be used instead of standard measuring devices. Our portable CED is efficient and simple when used in the field of medical physics.